Impact of Online Customer Reviews and Promotions on Customer Retention of Cosmetics in Shopee Mall through Purchase Decisions - Chintana, Andayu Juhawa; Barusman, Andala Rama Putra (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to analyze the impact of online reviews and promotions on customer retention of cosmetic products among students at the Faculty of Economics and Business, Universitas Bandar Lampung (FEB UBL), in the context of direct shopping on Shopee Mall. Methodology: A quantitative research method was used, with primary data collected through an online questionnaire distributed to 280 randomly selected respondents from a population of 936 students. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Results: The results show that both online reviews and promotions significantly influence purchase decisions. However, customer retention is only directly affected by promotions and purchase decisions, while online reviews indirectly influence retention through purchase decisions. Findings: The study highlights that promotions play a more significant role in customer retention than online reviews, which only indirectly affect retention through their impact on purchase decisions. Novelty: This research contributes to digital marketing literature by focusing on the cosmetics industry and the role of online reviews and promotions in customer retention, particularly in an e-commerce context. Originality: The study is original in its focus on the cosmetics industry, particularly in relation to e-commerce platforms like Shopee Mall. Conclusions: The study recommends that businesses prioritize effective promotional strategies and ensure a positive shopping experience to enhance customer retention. Type of Paper: Empirical research paper.